2022
DOI: 10.1021/acsami.2c00877
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Self-Healing First-Aid Tissue Adhesives with Outstanding Hemostatic and Antibacterial Performances for Trauma Emergency Care

Abstract: Soft-tissue trauma emergency caused by natural disasters and traffic accidents is highly prevalent, which can result in massive bleeding, pathogen infection, and even death. Although numerous tissue adhesives can bind to tissue surfaces and cover wounds, most of them still have several deficiencies, including long gelation time, poor adhesive strength, and anti-infection, making them inappropriate for use as first-aid bandages. Herein, injectable and self-healing four-arm-PEG-CHO/polyethyleneimine (PEI) tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…The hemostatic material should possess good biocompatibility to avoid delaying wound healing. Various sponges were co-cultured with L929 cells to assess their cytocompatibility using cell live/dead staining and CCK-8 assay, as fibroblasts are vital for wound healing ( He et al, 2021 ; Mei et al, 2021 ; Hao et al, 2022a ). The live/dead staining displayed in Figure 4A demonstrated that there were no significant differences in cell number and cell viability among sponges, and the cell viability was all higher than 98.5% ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…The hemostatic material should possess good biocompatibility to avoid delaying wound healing. Various sponges were co-cultured with L929 cells to assess their cytocompatibility using cell live/dead staining and CCK-8 assay, as fibroblasts are vital for wound healing ( He et al, 2021 ; Mei et al, 2021 ; Hao et al, 2022a ). The live/dead staining displayed in Figure 4A demonstrated that there were no significant differences in cell number and cell viability among sponges, and the cell viability was all higher than 98.5% ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue repair aims to develop biological substitutes for the repair or improvement of defective tissues, organ structures, etc. 172,173 Therefore, the materials used are required to be highly biocompatible and non-immunogenic, and when used in the body, also require the material to be effective in a wet environment. [174][175][176] Due to their good mechanical properties, biocompatibility, and tissue affinity, 177 adhesive materials can play an important role in various aspects of tissue repair.…”
Section: Tissue Repairmentioning
confidence: 99%
“…As shown in Figure 5A,B, the TNOTN and TNOTN−ACD hydrogels could effectively inhibit the growth of S. aureus and E. coli, as compared to the control group. Thanks to the strong antibacterial effect of the incorporated amine groups in the TNOTN block copolymers, 37 the TNOTN hydrogel was able to prevent the growth of S. aureus and E. coli with survival rates of 25 and 10%. By contrast, the TNOTN−ACD hydrogel could achieve a much better antibacterial performance to both bacteria and kill 94 and 95% of S. aureus and E. coli.…”
Section: Antibacterial Performance Of Hydrogelsmentioning
confidence: 99%